PELAKSANAAN PROGRAM OPTIMALISASI PEMENAFAATAN LAHAN PEKARANGAN MELALUI KELOMPOK WANITA TANI DI KECAMATAN TEBING TINGGI BARAT KABUPATEN KEPULAUAN MERANTI TAHUN 2018 - Risa Yulandani; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The implementation of the Yard Optimization Program through the Farmer Women Group in Tebing Tinggi Barat District will be carried out in 2018, the growth stage with the concept of a sustainable food house area (KRPL). At the stage of growing funding from the government in the amount of Rp.50,000,000 - for five KRPL activities, the aim of the KRPL activity is to empower households and communities in the provision of food and nutrition sources and increase awareness, role and community participation in realizing food consumption patterns that diverse, nutritionally balanced and safe (B2SA). However, there are some obstacles in the implementation of the Program for the Optimization of the Utilization of the House of Land through a group of women farmers in Tebing Tinggi Barat District, namely in the Insit Villag.                This study aims to determine the implementation of the Yard Utilization Optimization Program through a group of women farmers in Tebing Tinggi Barat District, Meranti Islands Regency in 2018 and the obstacles in implementing the Program, with the concept of policy implementation theory that researchers use, namely Merilee S. Grindle which states that the success of a policy implementation can be measured from the achievement process, namely the achievement of objectives to be achieved                The results of this study were the Implementation of the Yardland Utilization Optimization Program through farmer women groups in Tebing Tinggi Barat District, Meranti Islands Regency in 2018 the growth stage was not optimal. This happened because of the inhibiting factors, namely the non-fulfillment of the requirements set by the technical guidelines in the implementation of KRPL activities by the Asyfa farmer women's group in Insit Village, the determination of the location of the KRPL stage for the improper growth stage in Insit Village, the lack of information obtained by group members Asyfa farmer women in Insit Village regarding the growth stage KRPL activities, and the Asyfa Farmer Women's Group in Insit Village are not the majority of farmers. Keywords : Implementation, programs, KRPL activities